Profiling malaria infection among under-five children in the Democratic Republic of Congo. - Jacques B O Emina (Public Library of Science (PLoS), 2021)
Introduction In 2018, Malaria accounted for 38% of the overall morbidity and 36% of the overall mortality in the Democratic Republic of Congo (DRC). This study aimed to identify malaria socioeconomic predictors among children aged 6-59 months in DRC and to describe a socioeconomic profile of the most-at-risk children aged 6-59 months for malaria infection. Materials and methods This study used data from the 2013 DRC Demographic and Health Survey. The sample included 8,547 children aged 6-59 months who were tested for malaria by microscopy. Malaria infection status, the dependent variable, is a dummy variable characterized as a positive or negative test. The independent variables were child's sex, age, and living arrangement; mother's education; household's socioeconomic variables; province of residence; and type of place of residence. Statistical analyses used the chi-square automatic interaction detector (CHAID) model and logistic regression. Results Of the 8,547 children included in the sample, 25% had malaria infection. Four variables-child's age, mother's education, province, and wealth index-were statistically associated with the prevalence of malaria infection in bivariate analysis and multivariate analysis (CHAID and logistic regression). The prevalence of malaria infection increases with child's age and decreases significantly with mother's education and the household wealth index. These findings suggest that the prevalence of malaria infection is driven by interactions among environmental factors, socioeconomic characteristics, and probably differences in the implementation of malaria programs across the country. The effect of mother's education on malaria infection was only significant among under-five children living in Ituri, Kasaï-Central, Haut-Uele, Lomami, Nord-Ubangi, and Maniema provinces, and the effect of wealth index was significant in Mai-Ndombe, Tshopo, and Haut-Katanga provinces. Conclusion Findings from this study could be used for targeting malaria interventions in DRC. Although malaria infection is common across the country, the prevalence of children at high risk for malaria infection varies by province and other background characteristics, including age, mother's education, wealth index, and place of residence. In light of these findings, designing provincial and multisectoral interventions could be an effective strategy to achieve zero malaria infection in DRC.